Empirical Investigation into the impact of Corporate Governance on Stock Returns in Pakistan: Evidence from Financial Sector of Pakistan - Rooh, Samina; Wadood, Dr. Fazli; Malik, Muhammad Farooq (The journal of contemporary issues in business and government, 2021)
This study aims to investigate the impact of corporate governance on stock returns of commercial banks in Pakistan. Secondary data obtained and used from annual reports of banks and the Pakistan Stock Exchange database over a period from 2016-2020. The regression model is used to determine the influence of corporate governance on the stock returns in the banking sector. The results suggest that board size, a block of common shares, and individual & family block holdings have a significantly positive influence on stock returns while the board fraction, insiders’ block holdings, industrial block holdings, and firm leverage are negatively associated with stock returns. The findings provided practical implications for the firms striving to enhance better corporate governance mechanism to avail maximum stock returns.